SUBCLAVIAN CRUSH SYNDROME AND INAPPROPRIATE SHOCKS IN PATIENT WITH IMPLANTABLE CARDIOVERTER DEFIBRILATOR - Misic, Irena; Janusevski, Filip; Taleski, Jane; Risteski, Dejan; Popovska, Lidija (Journal of Morphological Sciences; Vol 5 No 3 (2022): JMS, 2022)
Subclavian crush syndrome may occur when the lead from cardiovascular implantable electronic device (CIED) is trapped between the clavicle and the first rib and the insulation layer is damaged, or conductor has been fractured. This complication carries an even greater risk if it involves a defibrillation electrode. Case report: We describe a case of a 68year old male patient with sudden onset of Implantable cardioverter defibrillator (ICD) activation- shocks delivery, more than ten times in the period of two hours, right before the admission to the emergency unit department. His ECG on admission shows rhythm of pacemaker with normal ventricular capture. The device interrogation revealed 53 episodes of ventricular fibrillation- false detection and delivery of multiple inappropriate shocks. Low impedance was detected of pace/sense electrodes <200â„¦, rise in shock impedance, ventricular oversensing episodes, and high pacing threshold. Due to Inappropriate ICD therapy the detection was turned off. Radiography findings have shown interruption of electrode â€“ continuity in a position corresponding to subclavian crush syndrome, thereby implantation of the new system was indicated. The intervention of new system implantation was performed without any complication in standard procedure, using left axillary vein approach. We inserted a new ventricular single coil defibrillation electrode and new ICD device. The patient was discharged in a good clinical condition. Physicians must demonstrate excellent understanding of lead designs, mechanism of lead fracture, diagnosis and management, in order to make the best decision for every individual patient. Inappropriate shocks are medical emergency and must be treated immediately. Individual approach in every patient should be mandatory. Keywords:subclavian crush syndrome, Implantable cardioverter defibrillator, lead fracture.